LEXICAL DENSITY AND READABILITY IN ENGLISH FOR JUNIOR HIGH SCHOOL VIII TEXTBOOK - Nurwahidah Ramadhani Waruwu; Johan Sinulingga; Yeni Erlita (Universitas Negeri Medan, 2018)
This study aimed to analyze and describe the lexical density and readability in English for Junior High School VIII textbook. It was conducted by using descriptive qualitative research. The textbook was published by Mediatama. It is used for the eighth grade of students in junior high school. The researcher used seven reading texts as the data. The lexical density was tested by using Ure’s formula and the readability was tested by using Flesch Reading Ease Formula. The result showed that the lexical density of the reading texts in English for Junior High School VIII textbook is above 40% which indicates that it has high lexical density. Lexical items (nouns, verbs, adjectives, and adverbs) play important role to influence the density of a text. The more lexical items in a text, the higher lexical density percentage will be and it also affects the readability of the reading texts. Then, the result also showed that the average readability score is 66 which falls into standard level. It indicates that the reading texts are readable for 8th grade students of junior high school but they still need teacher’s assistance to comprehend the texts. Keywords: Lexical Density, Readability, Flesch Reading Ease Formula.